Effectiveness, safety and efficacy of INTELLiVENT–adaptive support ventilation, a closed–loop ventilation mode for use in ICU patients – a systematic review. (2nd November 2021) - Botta, M.; Wenstedt, E.F.E.; Tsonas, A.M.; Buiteman-Kruizinga, L.A.; van Meenen, D.M.P.; Korsten, H.H.M.; Horn, J.; Paulus, F.; Bindels, A.G.J.H.; Schultz, M.J.; De Bie, A.J.R.
ABSTRACT: Introduction : INTELLiVENT–Adaptive Support Ventilation (INTELLiVENT–ASV), an advanced closed–loop ventilation mode for use in intensive care unit (ICU) patients, is equipped with algorithms that automatically adjust settings on the basis of physiologic signals and patient's activity. Here we describe its effectiveness, safety, and efficacy in various types of ICU patients. Areas covered : A systematic search conducted in MEDLINE, EMBASE, the Cochrane Central register of Controlled Trials (CENTRAL), and in Google Scholar identified 10 randomized clinical trials. Expert opinion : Studies suggest INTELLiVENT–ASV to be an effective automated mode with regard to the titrations of tidal volume, airway pressure, and oxygen. INTELLiVENT–ASV is as safe as conventional modes. However, thus far studies have not shown INTELLiVENT–ASV to be superior to conventional modes with regard to duration of ventilation and other patient–centered outcomes. Future studies are needed to test its efficacy.